Impact of Corn Cob-Derived Biochar in Altering Soil Quality, Biochemical Status and Improving Maize Growth under Drought Stress - Liaqat Ali; Natasha Manzoor; Xuqing Li; Muhammad Naveed; Sajid Mahmood Nadeem; Muhammad Rashid Waqas; Muhammad Khalid; Aown Abbas; Temoor Ahmed; Bin Li; Jianli Yan (Agronomy, 2021)
Biochar enhances soil fertility by improving the soil physical, chemical and microbiological properties. The aim of this study was to investigate the impact of corn cob-derived biochar on soil enzymatic activity, organic carbon, aggregate stability and soil microbial biomass carbon under drought stress. Biochar was prepared from crushed corn cobs pyrolyzed at 300 °C and 400 °C and applied at a ratio of 1% (w/w) and 3% (w/w) filled in pots. In each pot, three field capacity (FC) levels, i.e., 100, 70 and 40%, were maintained gravimetrically. Results showed that biochar application improved the growth (plant height and root length) and relative water content in maize leaves under drought stress, while it reduced electrolyte leakage compared to a control treatment. Aggregate stability was significantly (p ≤ 0.05) higher in biochar amended soil. Moreover, microbial biomass carbon and soil water also increased under drought stress at 70% FC and 40% FC, respectively, where 3% w/w (400 °C) biochar was applied. Among enzymes, β-glucosidase and alkaline phosphatase activity were improved with biochar application. The maximum organic carbon (240%, 246% and 249%, 254% more than control) was calculated in soils where 3% biochar pyrolyzed at 400 °C and 300 °C was mixed with soil, respectively. Similarly, the carbon pool index (CPI) and carbon management index (CMI) were also higher in biochar-amended soil as compared to control treatment. Conclusively, biochar amendment could effectively improve soil quality and maize growth under drought stress.